A fluorometric erythrophagocytosis assay using differentiated monocytic THP‐1 cells to assess the clinical significance of antibodies to red blood cells. Issue 10 (4th May 2021) - Balola, Abdelwahab Hassan Ahmed; Mayer, Beate; Bartolmäs, Thilo; Salama, Abdulgabar
Abstract : Background and Objectives: The significance of antibodies to red blood cells (RBCs) is variable and cannot be predicted solely by serological testing. A flow cytometry‐based erythrophagocytosis assay was established using phorbol 12‐myristate 13‐acetate (PMA)‐treated THP‐1 cells and RBCs labelled with PKH26 to assess allo‐ and autoantibodies to RBCs. Materials and Methods: THP‐1 cells were differentiated into macrophage‐like cells by treatment with PMA. RBC samples coated with alloantibodies or autoantibodies were obtained from 16 patients with autoimmune haemolytic anaemia of warm type (wAIHA) as well as from five pregnant women with warm autoantibodies. RBCs from healthy blood donors were used as controls. RBCs were labelled with the red lipophilic fluorescent dye PKH26 and incubated with PMA‐treated THP‐1 cells. After removal of nonadherent RBCs by washing and haemolysis of adherent RBCs, erythrophagocytosis was quantified by flow cytometry. Results: We observed significant phagocytosis of RBCs coated with clinically relevant alloantibodies (i.e. anti‐D and anti‐K) or autoantibodies from patients with active wAIHA, but not of those coated with alloantibodies (anti‐Ch) or autoantibodies from patients and pregnant women without haemolysis. Conclusion: The flow cytometry‐based erythrophagocytosis test described here is quantitative, highly reliable, and may be helpful for the assessment of the clinical significance of antibodies to RBCs.